PERSEPSI STAKEHOLDERSS TERHADAP PENGEMBANGAN DESA WISATA DESA BELEQ SEMBALUN LAWANG KECAMATAN SEMBALUN KABUPATEN LOMBOK TIMUR - Abd Hafiz Zulpan; Syech Idrus; Primus Gadu (Journal Of Responsible Tourism, 2023)
Beleq Village is the oldest village in Sembalun Lawang, Sembalun District, the potential of beleq village has a tourist attraction in the form of a culture that is still maintained authenticity, nature and also the daily activities of rural communities in general. However, the current condition due to the 2018 earthquake, the buildings of traditional houses and other facilities have been destroyed and have not been managed properly. This research uses a qualitative descriptive and quantitative descriptive approach. The focus of this study is to examine stakeholders' perceptions of the development of tourism villages, Beleq Sembalun Lawang Village, Sembalun District, East Lombok Regency. using cooper's theory of tourism destination development consisting of Attraction, Accessibility, Amenities, and Ancillary Service. Data collection using observation, interview, and questionnaire methods (Questionnaire). The results of the study based on questionnaires (Angket) and interviews showed stakeholders' perceptions of the development of tourism villages, Beleq Sembalun Lawang Village, Sembalun district, East Lombok regency. From the results of the questionnaire (Angket) after being calculated using the Interval scale which shows the average value is at a score of 3.43-4.23 that stakeholders are categorized as positive and very positive in the development of beleq village tourism village based on 4 aspects of tourism village development, namely acting as a tourist attraction actor, DTW manager, accessibility guard, lack of accessibility, as a manager and manager facilities such as lodging, general toilets. And the lack of an active role of society in managing additional services such as the occurrence of conflicts between groups. There are efforts that can be made to improve in the development of beleq village tourism villages, namely establishing good relations between stakeholders, improving the quality and quantity of tourist attractions.